Pyrrhonian language - Lozano-Vásquez, Andrea (Rónai – Revista de Estudos Clássicos e Tradutórios, 2020)
This article characterises how the Pyrrhonian Sceptic uses language to test if such use is susceptible to Dogmatic criticisms, especially from a Stoic perspective. It will examine two characterisations of that use. The first one, reported by Diogenes Laertius in his Lives of Eminent Philosophers 9.71-78, will be discussed as a logical use of human language broader than a philosophical one. The second characterisation depends on the discourse chosen by Timon of Phlius in his Silloi. In this work, the Epic catalogue shows itself as a powerful mechanism; it allows to report, to make history about philosophy itself and to offer an account of Pyrrho’s place in it without postulating substantive theses. This literary use and the previous philosophical one constitute the particular uses of Pyrrhonian language.